Potential CO2 reduction by fuel substitution to generate electricity in Malaysia - Masjuki, H.H. (Energy Conversion and Management, 2002)
Because of changing fossil fuel prices, sources and environmental consciousness, Malaysian utilities have been forced to change the type of energy sources to generate electricity. This new policy of electricity generation companies will change fuel use gradually from 70 gas, 15 coal, 10 hydro and 5 petroleum in the year 2000 to 40 gas, 30 hydro, 29 coal and only 1 petroleum in the year or 2020. These changes tend to reduce CO2 emission. This study attempts to predict the potential CO2 reduction due to these changes. The calculation is based on CO2 emission for unit electricity generated and the changing type of fuel percentages for electricity generation in Malaysia. The study found that the substitution will reduce CO2 emission from power plants in this country.